Interactive role of climate change on Economic growth - Farooq, Ammara (Journal of Medical Biomedical and Applied Sciences, 2014)
Climate change is a very uncertain and complex external phenomenon that affects the economic growth. The purpose of this paper is to study the role of climatic changes on economic growth globally as the climate effects are very crucial to evaluate the economic growth. Climate change has significant effects on the economy hence on the economic growth. In order to study the effect of climate change, all the effects of climate change will be discussed followed by the factors of economic growth and their interactive effect will be analyzedÂ